EXPLORING STUDENTS’ WEAKNESSES IN ENGLISH LANGUAGE AT SHAQRA UNIVERSITY (HURIMLAA CAMPUS), SAUDI ARABIA - Qahtani, Hijab (PEOPLE: International Journal of Social Sciences, 2018)
This research explores the reasons for the weaknesses of students of English Language at Shaqra University (Hurimlaa Campus), Saudi Arabia. University records show that students’ marks in these courses are deteriorating and this research paper explores the reasons that might account for this. Spurred by this phenomenal reality, the researcher developed a questionnaire incorporating twenty questions covering four dimensions: educational factors, cultural factors, social factors and attitudinal factors with the ultimate aim of attributing the students' status to justifiable reasons. The analytical method was adapted through which noticeable results showed that almost half of the sample experienced difficulties with both reading and sentence structuring. Nearly 70% of the students surveyed thought that learning English is crucial for communication and understanding. These results suggest that students are aware of the importance of and need for this language, and that these shortcomings can be attributed to educational factors including schools, university, instructors and modules. This humble research does not, however, answer all questions arising from the general stance of the English Language in Saudi Arabia. Further studies are still needed to cover other educational institutions.